Uretero-Iliac Artery Fistula: A Diagnostic and Therapeutic Challenge - Muhammad Z. Aslam; Ferhad Kheradmund; Nilay Patel; David Cranston (Advances in Urology)
Uretero-Iliac artery fistulas (UAFs) are very uncommon in urological practice. The rarity of this clinical entity may lead to a delayed or missed diagnosis which can result in life-threatening consequences. We present a case of a right ureteric and right external iliac artery fistula, its presentation, diagnosis, and management along with the review of the literature.